Constructive Journalism: Indonesian Journalists’ Perception and Implementation in the Covid-19 News - Ariestyani, Kencana (UI Scholars Hub, 2023)
Currently, the COVID-19 pandemic is getting under control, and people tend to adapt and live their lives in the new normal era. Despite that, media outlets carry on reporting the COVID-19 pandemic considering the information is still needed by the public. It is undeniable that journalists play an essential role in disseminating information about health risks to audiences. Nevertheless, news about health crises is often criticized for being sensational, incomplete, and inaccurate, giving rise to misunderstanding, panic, or even public neglect. Thus, it is hoped that the media outlets could present more constructive news to anticipate the effects of anxiety, panic, fatigue, stress, and depression encountered by the public after consuming information pertaining to COVID-19. This paper aims to explore how Indonesian journalists perceived the constructive journalism approach and its implementation in their journalistic work related to covering and reporting on Covid-19 news. Using constructive journalism theory and news framing and adapting qualitative research, the researchers conducted in-depth interviews with eight journalists from various media outlets spanning from television, online news media, and daily newspapers to the weekly news magazine. This research revealed that most Indonesian journalists are not familiar with constructive journalism. Nevertheless, they conceived the approach of constructive journalism. The concept has been implemented in covering Covid-19 news by Indonesian journalists though it has not been shown as the optimal undertaking due to external and internal factors. As a result, there are still accounts of Covid-19 that could trigger public anxiety and cause them to endure other adverse psychological effects after consuming news stories. This research suggests that media outlets and Indonesian journalists could consider and comprehensively grasp the constructive journalism approach in their daily journalistic works to anticipate those negative psychological impacts.